Cycle Count Dan Quality Control dalam Pendistribusian Barang - Subandi Subandi; Sumirahwati Sumirahwati; Anugerah Ramadhan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
PT Agility International is a company that provides warehousing services. The purpose of this study is to identify and analyze the effects of cycle count and quality control on the distribution of goods. The research method used was quantitative method using questionnaires and library data as the data collection methods. The data was analyzed using multiple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The result shows that there is a significant impact between the effect of cycle count and quality control on the distribution of goods, meaning that each increase in cycle count X1 is followed by an increase in Y distribution and each increase in quality control X2 is followed by an increase in distribution. With r=0,337 as the coefficient correlation, there is a low impact between X1, X2 and Y. Coefficient of determination test shows 11,35% meaning that there is a positive contribution by the cycle count and quality control to the distribution of goods. On the other hand, 88,65% of it is determined by other factors affecting X1 and X2 variables to Y.